2020
DOI: 10.1136/postgradmedj-2020-137868
|View full text |Cite
|
Sign up to set email alerts
|

Association between response rates and monetary incentives in sample study: a systematic review and meta-analysis

Abstract: ObjectiveTo investigate the effect of monetary incentive and the dose–response relationship of participants’ response rates in surveys.MethodsThree databases were searched for randomised controlled trials (RCTs) that investigated the effect of monetary incentives on participants’ first and final response rates. First response is defined as the responses after the participant was initially contacted and final response is defined as the responses after several reminders were sent. The potential dose–response rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 119 publications
2
6
0
Order By: Relevance
“…Our study is consistent with previous literature showing that prenotifications can increase response rates, particularly for electronic surveys [ 4 , 10 , 20 - 22 , 39 ]. We also observed higher response rates when including a gift or monetary incentive; however, prior studies only observed an increase with monetary incentives [ 39 - 42 ] and not with other incentives [ 43 - 46 ]. Interestingly, in cancer patients, both a small gift for all invited individuals or a gift card for those who completed the survey led to similar response rates.…”
Section: Discussionsupporting
confidence: 93%
“…Our study is consistent with previous literature showing that prenotifications can increase response rates, particularly for electronic surveys [ 4 , 10 , 20 - 22 , 39 ]. We also observed higher response rates when including a gift or monetary incentive; however, prior studies only observed an increase with monetary incentives [ 39 - 42 ] and not with other incentives [ 43 - 46 ]. Interestingly, in cancer patients, both a small gift for all invited individuals or a gift card for those who completed the survey led to similar response rates.…”
Section: Discussionsupporting
confidence: 93%
“…Our study is consistent with previous literature showing that prenotifications can increase response rates, particularly for electronic surveys [4,10,[20][21][22]39]. We also observed higher response rates when including a gift or monetary incentive; however, prior studies only observed an increase with monetary incentives [39][40][41][42] and not with other incentives [43][44][45][46].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, several studies have investigated influential factors of trial recruitment and participation. Key influential factors include altruistic motives [10][11][12][13][14], such as contribution to scientific research, financial incentives [13,[15][16][17][18], and the doctor-patient relationship [11,19,20].…”
Section: Introductionmentioning
confidence: 99%